System Engineering and Dependability: Methodology of Model Synchronization between System Architecture Models and Risk Analysis. Issue 4 (10th January 2020) - Legendre, Anthony; Lanusse, Agnès; Rauzy, Antoine
ABSTRACT: Modern industry faces new challenges making classical organization in "disciplinary silos" ill‐adapted to demands for complex and evolving systems. We advocate promoting inter‐team communication in a "Multidisciplinary Organization" can manage complexity better: it allows early problem discovery, offers solutions to more complex issues, and favors early solution emergence. Indeed the transition to such organization requires new collaborative processes and methods to integrate various engineering fields earlier and along the development cycle. In this paper, we propose a collaborative approach to set‐up adapted modeling and methodological practices in the enterprise. It leverages the rising interest for Model‐Based Systems Engineering and related modeling technologies to offer a new approach to different engineering discipline model synchronization to support their collaboration. This approach considers the studied system context (under several viewpoints), applied processes, applied methods, and viewpoints produced by engineers. We illustrate it by creating a collaboration framework between two particular engineering fields: system architecture design and avionics applicative safety analysis at different life cycle stages.